Hubungan Karakteristik Ekonomi Ddengan Pengetahuan Nelayan Ikan Demersal di Kecamatan Wangi-Wangi Selatan Kabupaten Wakatobi - Mardin, Mardin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The research objectives were: (1) to describe the fishermen’s characteristic of economic, (2) to describe the fishermen’s knowledge on demersal fish, and (3) to determine the correlation between an economic characteristic and the fishermen’s knowledge. The data collection was conducted in South Wangi-Wangi sub-district, district of Wakatobi in July through September 2008. The respondents were the fishermen of demersal fish selected by simple random sampling from five villages included Mola Selatan, Mola Samaturu, Mola Bahari, Mola Nelayan Bhakti, and Mola Utara. Data were collected through direct interview using questionnaires. Pearson’s Correlation analysis was used to analyze the data. The results indicated that: (1) the fishermen’s asset, operational cost, and saving define in fewer categories. More than half of respondent had no diversity of business; the respondent income defines in fairly category, while the respondent saving defines in less category. (2) More than half of respondent defines in the fair category on seven component of knowledge, while one another component i.e fishermen’s knowledge of financial capital defines in less category. (3)There were two characteristics of economic that significantly correlated to the fishermen’s knowledge. They were the fishermen’s asset and the diversity of business. The fishermen’s assets correlated to fishermen’s knowledge positively, while the fishermen’s diversity of business correlated negatively to the fishermen’s knowledge.